2004
DOI: 10.1099/vir.0.80385-0
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of alternative oxidase protein sequences enhances the spread of viral vectors in resistant and susceptible plants

Abstract: The alternative oxidase (AOX) is the terminal oxidase of the cyanide-resistant alternative respiratory pathway in plants and has been implicated in resistance to viruses. When tobacco mosaic virus (TMV) vectors were used to drive very high levels of expression of either AOX or AOX mutated in its active site (AOX-E), virus spread was enhanced. This was visualized as the induction of larger hypersensitive-response lesions after inoculation onto NN-genotype tobacco than those produced by vectors bearing sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 53 publications
2
38
1
Order By: Relevance
“…It has been suggested that tobacco and tomato cyanideinduced resistance to virus is mediated by AOX, which would contribute to the signal transduction pathway leading to resistance (Chivasa and Carr, 1998;Fu et al, 2010). Strikingly, when overexpressing either the native AOX or a version of AOX mutated at its active site, tobacco mosaic virus vectors increase systemic movements in Nicotiana benthamiana (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that tobacco and tomato cyanideinduced resistance to virus is mediated by AOX, which would contribute to the signal transduction pathway leading to resistance (Chivasa and Carr, 1998;Fu et al, 2010). Strikingly, when overexpressing either the native AOX or a version of AOX mutated at its active site, tobacco mosaic virus vectors increase systemic movements in Nicotiana benthamiana (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent studies have also shown that if plants lacking AOX are environmentally stressed, the damage is greater either in terms of ROS production or cell death (Giraud et al 2008;Watanabe et al 2008). To date, only a few studies have examined the changes in the AOX content in a whole plant challenged with TMV, and all of these have been conducted with tobacco plants (Ordog et al 2002;Gilliland et al 2003;Murphy et al 2004). These previous studies have focused on the involvement of AOX in the anti-TMV defense response using transgenic lines with altered AOX gene expression and alternative-pathway capacity.…”
Section: Aox Activity Reduced Ros Accumulation Under a Tmv-infected Cmentioning
confidence: 97%
“…These previous studies have focused on the involvement of AOX in the anti-TMV defense response using transgenic lines with altered AOX gene expression and alternative-pathway capacity. To our knowledge, only Murphy et al (2004) have analyzed the ROS production during this process in tobacco plants. The authors found that increased amounts of H 2 O 2 accumulated not only in AOX-overexpressing lines but also in lines transformed with AOX that carried a mutation in its active site, and they speculated that abnormal levels of AOX proteins could indirectly perturb the AOX-mediated detoxification of ROS in the mitochondria and thus the mitochondrial redox balance.…”
Section: Aox Activity Reduced Ros Accumulation Under a Tmv-infected Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when Tobacco mosaic virus (TMV) vectors induced a high expression level of alternative oxidase (AOX), the virus spread was faster, and the symptom became more severe, in spite of the virus replication level (Murphy et al 2004). Another example is the TCV-satC (a satellite RNA associated with TCV) system, where symptoms are substantially enhanced and virus levels are signiWcantly reduced (Sun and Simon 2003).…”
Section: Introductionmentioning
confidence: 98%